TCN5 - Teaching computer networks in a free immersive virtual environment - Voss, Gleizer Bierhalz (2014)
Teaching technical themes in the area of Computer Networks involves difficult concepts to be understood in the traditional educational way, i.e. statically. At the same time, technological advances have created many opportunities in education, requiring the development of new pedagogical practices that contribute to the process of teaching and learning. The creation of immersive virtual environments and the addressing of issues related to context-aware computing can support this process. For that, in this dissertation it was developed an immersive virtual environment for teaching Computer Networks that uses learner context information -e.g. technology, cognitive style, and quality of context-, while providing a significant learning from the integration and interaction between users and technology. To achieve the objectives of this study, an exploratory research with a case study was performed in order to verify whether the use of an immersive virtual environment can facilitate and/or improve the process of learning the discipline of Computer Networks. The construction of this environment, named TCN5, has as basis four main elements, these being,WampServer, OpenSimulator, Sloodle and UVLEQoC Moodle, which adds features from modules like U-SEA 2.0 and SEDECA 2.0, in addition to Bootstrap theme, applying QoC parameters and metrics about the information collected in the environment, aiming to ensure the suitability of the connection for the preferences and needs of the students. In order to verify the practical feasibility of the work and the usage of the environment through mobile devices, a case study was conducted, which showed that despite mobile technologies allow the realization of most of the proposed activities, there are still some technological limitations that make difficult the usage of such devices in the educational context. At the same time, a comparative analysis between different viewers for virtual worlds was performed, pointing out advantages and disadvantages by considering aspects of available resources for processing and supported file types. Finally, a non-experimental study was conducted, using a Pedagogical Architecture, which served as the basis for the use and evaluation of the environment by a group of 25 students from the Computer Networks discipline of Computer Science program at the Federal University of Santa Maria. The results obtained during the evaluation with students accomplished the desired expectations, achieving a rating of "Excellent" on the scale of the SUS usability test and a considerable increase in the average obtained in the elaboration of the conceptual maps after using TCN5, an indication that the environment helped, at least in part, to the construction of knowledge of this group, despite the limitations and difficulties encountered during its development.